Analysis of Academic Anxiety in Students - Sepriadi,; Pratiwi, Monica Dara (International Journal of Psychosocial Rehabilitation, 2020)
The problem in this study is that there are still a number of final year students who have not yet completed the thesis. This is allegedly due to academic anxiety experienced by final year students. This study aims to determine the extent of academic anxiety in academic writing of the Thesis of the Sport Education Department. This research type is descriptive research. The population is 300 thesis subjects of Sports Education students. The sampling technique of this study was random sampling by using Disproportionate Stratified Random Sampling method. From total population, 36 students were selected as research samples. The instruments was questionnaire and Data analysis techniques used descriptive presentation techniques.The results of the study were: (1) the emotional reaction can be known, 2.8% of students have an anxiety level in the very hard category, 61.1% of students have an anxiety level in the hard category, 36.1% students have an anxiety level in the moderate category ( 2) cognitive reactions 77.8% of students have anxiety levels in the hard category 22.2% of students have anxiety levels in the medium category (3) physiological reactions 11.1% of students have anxiety levels in very hard categories, 75.0% of students have anxiety levels in the severe category 13.9% of students have anxiety levels in the moderate category.overall the level of academic anxiety in writing thesis, students of the Sports Education Department, Faculty of Sports, Universitas Negeri Padang was in the classification of hard anxiety levels with category at the level of 65.32%.